Ultrastructural localization of actin and actin-binding proteins in the nucleus - Dingová, Hana; Fukalová, Jana; Maninová, Miloslava; Filimonenko, Vlada V; Hozák, Pavel (Histochemistry and cell biology, 2009)
Nuclear actin plays an important role in such processes as chromatin remodeling, transcriptional regulation, RNA processing, and nuclear export. Recent research has demonstrated that actin in the nucleus probably exists in dynamic equilibrium between monomeric and polymeric forms, and some of the actin-binding proteins, known to regulate actin dynamics in cytoplasm, have been also shown to be present in the nucleus. In this paper, we present ultrastructural data on distribution of actin and various actin-binding proteins (alpha-actinin, filamin, p190RhoGAP, paxillin, spectrin, and tropomyosin) in nuclei of HeLa cells and resting human lymphocytes. Probing extracts of HeLa cells for the presence of actin-binding proteins also confirmed their presence in nuclei. We report for the first time the presence of tropomyosin and p190RhoGAP in the cell nucleus, and the spatial colocalization of actin with spectrin, paxillin, and alpha-actinin in the nucleolus.
Keywords: financování organizované; HeLa Cells; Nuclear Proteins; GTPase-Activating Proteins; lymfocyty; jaderné proteiny; spektrin; proteiny aktivující GTPasu; mikrofilamentové proteiny; lidé; HeLa buňky; paxilin; Cell Nucleus; Spectrin; aktinin; Financing, Organized; buněčné jádro; Actinin; aktiny; Actins; Tropomyosin; Lymphocytes; tropomyosin; Microfilament Proteins; Paxillin; Humans